KPT and UMP donate to help students family - Mimi Rabita, Abdul Wahit (2021)
JERANTUT, 5 February 2021 - The Minister of Higher Education, Datuk Seri Dr. Noraini Ahmad was present to meet and greet the family of the late Uqail Iskandar Zulkernain, a student of Universiti Malaysia Pahang (UMP) who passed away last month.